Universal Space of Far Eastern Federal University - Moor, Valery (project baikal, 2015)
The article observes designing and construction of one of the new university complexes in Russia, Far Eastern Federal University. It analyzes the town-planning decision, the spatial structure, drawbacks and contradictions occurred during operation of the university campus.